1972
DOI: 10.1002/j.1556-6978.1972.tb01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences among Male A, B, and C Master's Degree Candidates in a Counseling Practicum

Abstract: Little or no research has been done on the counseling practicum grade as a measure of counseling effectiveness. This study explored the intellective and nonintellective differences among males with A, B, and C grades in the counseling practicum. Significant differences among grade categories were observed on 7 of 17 variables. The nature and direction of the differences among males with grades of A, B, or C suggested that practicum grades tend to make valid discriminations between candidates with high and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The present results suggest that the GATB Verbal Aptitude scale and the MIQ may be useful in the selection of applicants for graduate study in counseling psychology and that the SVIB-W may be useful with female applicants. The findings for the GATB Verbal Aptitude scale are consistent with those of Jansen et al (1970Jansen et al ( , 1972, who reported a relationship between scores on the Cooperative English Tests and two criteria, overall competence as determined at the end of an evaluation seminar and grades in a counseling practicum.…”
Section: Discussionsupporting
confidence: 84%
“…The present results suggest that the GATB Verbal Aptitude scale and the MIQ may be useful in the selection of applicants for graduate study in counseling psychology and that the SVIB-W may be useful with female applicants. The findings for the GATB Verbal Aptitude scale are consistent with those of Jansen et al (1970Jansen et al ( , 1972, who reported a relationship between scores on the Cooperative English Tests and two criteria, overall competence as determined at the end of an evaluation seminar and grades in a counseling practicum.…”
Section: Discussionsupporting
confidence: 84%
“…Jansen, Robb, and Bonk (1972) have suggested that three distinct patterns of characteristics typified "A," "B," and "C" male practicum students. Jansen, Robb, and Bonk (1972) have suggested that three distinct patterns of characteristics typified "A," "B," and "C" male practicum students.…”
Section: Rating Systems In Practicummentioning
confidence: 99%